Vision based stabilization of a quadrotor using nested saturation control approach - Zamudio, Z.; Lozano, R.; Torres, J.; Rullan-Lara, J. L. (2011 15th International Conference on System Theory, Control, and Computing, 2011)
The problem of estimating position and orientation (pose) of an object in real time constitutes an important issue for vision-based control of robots. In this paper, we present a vision based controller design and its implementation on a quadrotor. The dynamic model is obtained using the well known Euler-Lagrange approach. Experiment results show good performance of the proposed controller using "real-time" optical flow and image processing.